Model Komunikasi Gastronomi Melalui Pemanfaatan Virtual Reality dalam Mendukung Promosi Pariwisata Kuliner Indonesia - Nofiasari, Wida; Susanto, Andi Heru; Alpian, Alpian (Unitri Press, 2024)
The archipelago's gastronomy is very diverse, one of which is Javanese culinary in Jogjakarta which was influenced by the Ancient Mataram period in the 8th century. The development of digital technology has encouraged an effective gastronomic communication model by utilizing in promoting Indonesian culinary tourism. The aim of this research is to find out how the gastronomic communication model through supports the promotion of Indonesian culinary tourism. This study uses a qualitative approach with a virtual ethnography method with 5 informants. The results of the research are (1) There are three categories of people enjoying culinary tourism, namely the need to eat simply, food as gastrodiplomacy other countries and food as an economic tourist attraction, (2) Javanese culinary tourism has developed since the time of Ancient Mataram as evidenced by inscriptions and reliefs at Borobudur and Prambanan Temples, (3) Gastronomic communication is carried out in three ways, namely the creation of a Gastronomic Museum, educational seminars on gastronomy and gastronomic diplomacy to foreign nations. The research conclusion is that Virtual Reality-based gastronomic communication was developed through the creation of a Gastronomic Museum which can support the promotion of Indonesian culinary tourism to the general public, especially the millennial generation, with educational, historical and entertainment function. Apart from that, the introduction of Indonesian culinary delights was carried out through outreach to universities and gastronomic diplomacy to other countries. Abstrak Gastronomi Nusantara sangat beragam salah satunya kuliner Jawa di Jogjakarta yang dipengaruhi masa Mataram Kuno di abad ke-8 Masehi. Perkembangan teknologi digital mendorong adanya model komunikasi gastronomi yang efektif dengan memanfaatkan virtual reality dalam mempromosikan pariwisata kuliner Indonesia. Tujuan penelitian ini adalah untuk mengetahui bagaimanakah model komunikasi gastronomi melalui virtual reality dalam mendukung promosi pariwisata kuliner Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan metode etnografi virtual dengan informan berjumlah 5 orang. Hasil penelitian adalah (1) Ada tiga macam kategori orang menikmati wisata kuliner yaitu kebutuhan makan semata, makanan sebagai gastrodiplomasi kepada negara lain dan makanan sebagai daya tarik wisata secara ekonomi, (2) Wisata kuliner Jawa sudah berkembang sejak zaman Mataram Kuno dibuktikan adanya prasasti dan relief di Candi Borobudur dan Prambanan, (3) Komunikasi gastronomi dilakukan melalui tiga cara yaitu pembuatan Museum Gastronomi Virtual Reality, edukasi seminar mengenai gastronomi dan diplomasi gastronomi kepada bangsa asing. Kesimpulan penelitian adalah komunikasi gastronomi berbasis Virtual Reality dikembangkan melalui pembuatan Museum Gastronomi Virtual Reality yang dapat mendukung promosi pariwisata kuliner Indonesia kepada masyarakat umum khususnya generasi milenial dengan fungsi edukasi, sejarah dan hiburan. Selain itu dilakukan pengenalan kuliner Nusantara melalui sarana sosialisasi kepada perguruan tinggi dan diplomasi gastronomi kepada negara lain.